Numerical simulation of crack propagation in reinforced concrete deep beams - Goh, Yee Hao (2022)
Reinforced concrete deep beam is a beam with a smaller shear span to depth ratio and is popular to be used as shear stress transfer component in high rise buildings. The cracking behaviour analysis of deep beam is a study aspect with high research value, but experimental analysis for cracking behaviour analysis can be costly. ABAQUS software helps simplify the parameter study of cracking behaviour for deep beam through Finite Element Analysis (FEA) method. In this study, an experimental result of deep beam published by Zhang and Tan (2007) was adopted for numerical modelling. Although failure load for numerical result reflected 20.6 % higher than experimental result, both results resembled well for the trend of the load-deflection curve and proven the reliability of numerical modelling technique. The verified model was used for performing the study of the parameter that affect the deep beam behaviour in term of strength and crack, which included shear span to depth ratio, longitudinal reinforcement diameter and position of shear link. The loaddeflection curves were plotted to evaluate the strength behaviour of deep beam with changing of parameter while the von Mises stresses contour, plastic strain magnitude diagram and concrete tension damage contour were captured to evaluate the crack propagation and the changes of crack pattern with changing of parameter. As the result, smaller shear span to depth ratio showed an obvious enhancement ranging from 3.95 % to 10.13 % for deep beam shear capacity and less severe crack. Moreover, changing longitudinal reinforcement diameter brings very little enhancement effect with not more than 10 % in shear capacity and it decreases to 1.09 % when bar diameter goes beyond 20 mm, only the flexural behaviour of deep beam is affected instead of shear behaviour. Lastly, position of shear link is sensitive to deep beam behaviour. When it placed beyond the concrete compressive strut zone, it shows 7.6 % reduction in shear capacity as compared to control beam, and it shows 1.27 % enhancement when placed within the region. The reliability of numerical analysis for deep beam behaviour is proven and three insightful findings to different parameters that affecting deep beam behaviour are contributed.